Impact of the new South African and German constitutions on labour law: a comparative analysis - Woehlert, Silke (Centre for Law and Society, 2023)
The main concern of the study is to present some reflections on the impact which the new South African and German constitutions have on labour law and labour relations. It assesses the efficacy of the two constitutions in the development of labour law and promotion of various employees rights such as freedom of association, collective bargaining, workplace democracy and industrial conflict resolution. The content of human rights standards and the role of the state in the exercise of such rights are considered in interpreting the constitutions. The study locates labour relations within the context of International Labour Organisation standards. The relevance of Conventions no. 87 and no. 98 of the International Labour Organisation on the right to form and belong to unions and to bargain collectively and to strike are examined. There are also other factors, which have to been taken into account. These factors include the different historical development and the different economic and political contexts of both legal systems. In this regard, the study discusses the problems and benefits of each system. The contention is made that there is a profound effect on employment and labour law where fundamental worker rights have been adopted. Continental systems of labour laws as in Germany have experienced a different judical performance as a result of the constitutional entrenchment of worker rights. The new South African constitution is going to have a profound effect on labour law because the constitution is supreme law and enumerates workers rights wich the Constitutional Court has the power to adjudicate on the validity of all such laws. The study concludes that the South African constitution will achive success and improve the working lives of employeers in many aspects.